Malik Mahmud Local Strongmen? - Arif Akbar (Universitas Muhammadiyah Malang, 2019)
The Helsinki MoU agreed by the Indonesian Government and the Free Aceh Movement provided an opportunity for Aceh to have a customary institution called the Wali Nanggroe institution. This opportunity was used by the DPRA which was dominated by the Aceh Party by confirming Malik Mahmud Alhaitar as the Naggroe Aceh Mayor, in the Aceh Party structure Malik Mahmud was one of the leaders of this local Party, so it was possible to have a dual role played by the figure of Wali Naggroe. The inauguration of Malik Mahmud as the Wali Nanggroe also indirectly gave rise to a local figure of Strongmen within the structure of the Acehnese community, given the position of the Wali Nanggroe as a position that was highly respected in the structure of Acehnese people's lives. Moving on from the above problems, this study wants to see how the role of the State in giving birth to local Strongmen within the structure of Acehnese society. This research borrows his theorist Jonh T Sidel and Migdal who have formulated how the formation of local Strongmen or bossism and the characteristics of both. Based on the results in the field, it shows that the local Strongmen could emerge because of the involvement of the State in them, the involvement of the State is not limited to giving the opportunity for the birth of local Strongmen but more than that, the State also provides legal standing for local StrongmenKeywords :Local Strongmen, Wali Nanggroe